Zoonotic Transmission of Campylobacter jejuni to Caretakers From Sick Pen Calves Carrying a Mixed Population of Strains With and Without Guillain Barré Syndrome-Associated Lipooligosaccharide Loci - St. Charles, Jessica L.; Brooks, Phillip T.; Bell, Julia A.; Ahmed, Husnain; Van Allen, Mia; Manning, Shannon D.; Mansfield, Linda S. (Frontiers in Microbiology, 2022)
Campylobacter jejuni causes foodborne gastroenteritis and may trigger acute autoimmune sequelae including Guillain Barré Syndrome. Onset of neuromuscular paralysis is associated with exposure to C. jejuni lipooligosaccharide (LOS) classes A, B, C, D, and E that mimic and evoke antibodies against gangliosides on myelin and axons of peripheral nerves. Family members managing a Michigan dairy operation reported recurring C. jejuni gastroenteritis. Because dairy cattle are known to shed C. jejuni, we hypothesized that calves in the sick pen were the source of human infections. Fecal samples obtained from twenty-five calves, one dog, and one asymptomatic family member were cultured for Campylobacter. C. jejuni isolates were obtained from thirteen calves and the family member: C. coli from two calves, and C. hyointestinalis from two calves. Some calves had diarrhea; most were clinically normal. Typing of lipooligosaccharide biosynthetic loci showed that eight calf C. jejuni isolates fell into classes A, B, and C. Two calf isolates and the human isolate possessed LOS class E, associated mainly with enteric disease and rarely with Guillain Barré Syndrome. Multi-locus sequence typing, porA and flaA typing, and whole genome comparisons of the thirteen C. jejuni isolates indicated that the three LOS class E strains that included the human isolate were closely related, indicating zoonotic transmission. Whole-genome comparisons revealed that isolates differed in virulence gene content, particularly in loci encoding biosynthesis of surface structures. Family members experienced diarrheal illness repeatedly over 2 years, yet none experienced GBS despite exposure to calves carrying invasive C. jejuni with LOS known to elicit antiganglioside autoantibodies.